2021
DOI: 10.1016/j.tranon.2021.101146
|View full text |Cite
|
Sign up to set email alerts
|

High throughput proteomic and metabolic profiling identified target correction of metabolic abnormalities as a novel therapeutic approach in head and neck paraganglioma

Abstract: Highlights SDH mutations are responsible for the occurrence of head and neck paragangliomas (HNPGLs). Deregulation of oxidative phosphorylation (ROS) in association with metabolism may play an important role in HNPGLs. NDUFA 2, 4 and 10 showed the most significant deregulaion in HNPGLs, and this deregulation can be corrected by metformin. Metformin exerts inhibitory effects on HNPGL cells via reduced level of reactive oxygen species and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…34 Succinate dehydrogenase (SDH), a formidable constituent of the respiratory chain complex II and a vanguard of energy metabolism, assumes a dual mantle as a cardinal component within both the tricarboxylic acid cycle and the mitochondrial respiratory chain’s complex II, thereby orchestrating oxidative phosphorylation. 35 Under the ambience of hypoxia, the genetic malformations bedecking the SDH subunit-encoding genes engender an accrual of succinate, thereby prompting the restraint of HIF-1 prolyl hydroxylases, thereby perpetuating the stabilizing trajectory of HIF-1. Supplementary to this, the aberrant functioning of SDH precipitates the generation of reactive oxygen species (ROS), a cardinal consequence of SDH inhibition’s dual identity within the respiratory chain’s complex II, an outcome imbued with the potency of directly potentiating the stabilization of HIF-1.…”
Section: Discussionmentioning
confidence: 99%
“…34 Succinate dehydrogenase (SDH), a formidable constituent of the respiratory chain complex II and a vanguard of energy metabolism, assumes a dual mantle as a cardinal component within both the tricarboxylic acid cycle and the mitochondrial respiratory chain’s complex II, thereby orchestrating oxidative phosphorylation. 35 Under the ambience of hypoxia, the genetic malformations bedecking the SDH subunit-encoding genes engender an accrual of succinate, thereby prompting the restraint of HIF-1 prolyl hydroxylases, thereby perpetuating the stabilizing trajectory of HIF-1. Supplementary to this, the aberrant functioning of SDH precipitates the generation of reactive oxygen species (ROS), a cardinal consequence of SDH inhibition’s dual identity within the respiratory chain’s complex II, an outcome imbued with the potency of directly potentiating the stabilization of HIF-1.…”
Section: Discussionmentioning
confidence: 99%
“…ND-UFA2 and NDUFB9 are auxiliary subunits of the mitochondrial membrane respiratory chain NADH dehydrogenase (complex I). Zhigang Wang et al [20] demonstrated through mutational analysis of 14 patients that significant up-regulations of NDUFA2, NDUFA10 and NDUFA4 were involved in the development of head and neck paragangliomas (HNPGLs). NDUFA2 has been found to be frequently targeted by tumorigenic microRNAs in colorectal cancer (CRC) [21].…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations have been suggested by Hujber et al regarding human glioma cells containing IDH mutation [ 20 ]. Interestingly, Wang et al showed that SDHx tumors present decreased complex II activity, associated with increased activity of the rest of OXPHOS complexes (I, III and IV), suggesting a compensatory effect [ 21 ]. The decrease in OXPHOS gene expression has been shown earlier in SDHx mutated PCCs/PGLs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%